(The audio and visual means of Da'wa through the World Wide Web (meaning, importance and models - Harraz, Attia El Mursi Mostafa; El Basaty, Mohamed El Sayed (Journal of Islamic Sciences, 2018)
The research has included the definition of Da'wa methods in Islamic audio and visual sites through the World Wide Web and its importance in the call to God and presented the Da'wa models of these contemporary means. The contemporary means of Da'wa in Islamic audio and visual sites through the World Wide Web (meaning, importance and models) the means divided to audio, video and social media. The research came in the preface, four researches and a conclusion. The preface gave definitions to the main terms of research in language and terminology, which are the means of Da'wa and the World Wide Web. The first research discussed audio means essence, defined its importance and presented models used in Da'wa. The second research presented the audiovisual means of Da'wa(its essence, importance and models used in Da'wa). The third research defined the chat rooms, its importance and mentioned examples of the use of (PALTAIK) in the Islamic Da'wa. The fourth research defined the social media and cognize its importance and represents some activities in Da'wa through some accounts and platforms like (Facebook) and (Twitter). The research was concluded with the most important findings, recommendations, list of references and sources.
Keywords: Means; Da'wa; Islamic; Web; Video; Paltalk; Facebook; Twitter